Determining Leading Industries in Optimizing Downstream Potential of North Sumatra Province: an Input-Output Approach - Nur Azizah Arianggi Suryaatmaja; Iqram Ramadhan Jamil; Ananda Sintia Putri (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
The economic condition of North Sumatra province due to the COVID-19 pandemic has weakened, especially on the supply side, by a negative growth rate in the productivity of the business sector. Industrial downstream could boost economic recovery and inclusive development by creating solid domestic relations with supporting regional industries and increasing high-value-added exports. This study aims to identify priority sectors and analyze the impact of these priority sectors on the manufacturing industry in North Sumatra based on linkage analysis using data during the economic recovery. The data from the I-O table of North Sumatra province in 2016 was sourced from the Central Statistics Agency (BPS) and covered 50 economic sectors. In addition, this study also used data on the GRDP of North Sumatra in 2021. This study applied the RAS Method to determine the value of the technical coefficient matrix of the input-output table in 2021. Then, this study also calculated the value of forward and backward linkages, output multiplier, value-added multiplier, and inoperability. The results revealed three priority sectors in North Sumatra, the Food and Beverage industry; the Base Metal industry; and the Paper and Paper Goods industry, Printing and Reproduction of Recording Media. The study recommends that the government encourage the acceleration of infrastructure by providing financial and policy support to these leading sectors and facilitating distribution channels so that industrial downstream runs optimally to the overall economy.